Taiwanese Dermatological Association (TDA) consensus recommendations for the definition, classification, diagnosis, and management of hidradenitis suppurativa - Yi-Hua Liao; Chia-Bao Chu; Chung-yee Rosaline Hui; Cheng-Yuan Li; Sheng-Yao Lin; Han-Chi Tseng; Yen-Jen Wang; Jennifer Wu; Wei-Wen Yu; Sheau-Chiou Chao (Journal of the Formosan Medical Association)
Hidradenitis suppurativa (HS) is a chronic inflammatory follicular disease characterized by painful, recurrent, inflamed lesions most commonly occurring in the axillary, inguinal, and anogenital regions. HS can inflict immense physical and psychological impact on patients who suffer from this distressing disease. Management of HS generally requires combining various medical and procedural treatment modalities; however, the disease is often recalcitrant to conventional treatments. In light of recent evidence supporting the effectiveness of biologic agents in the treatment of HS, the Taiwanese Dermatological Association established an expert panel of nine dermatologists to develop consensus statements aimed to provide up-to-date evidence-based guidance in optimizing HS patient management in Taiwan. The recommendations described in the statements were summarized in a management algorithm in terms of general care, topical treatment, systemic treatment, and procedural treatment.